Association between dietary intake of selenium and chronic kidney disease in US adults: a cross-sectional study of NHANES 2015–2018 - Pi, Ying; Liao, Xianyong; Song, Xiaodan; Cao, Yuyu; Tang, Xiaona; Lin, Guobing; Zhong, Yanghong (Frontiers in Nutrition, 2024)
Background: Chronic kidney disease (CKD) is currently a widespread chronic illness, and its development is influenced by nutrients. Selenium plays a crucial role in the intervention and therapy of various chronic illness. In this study, we aimed to investigate the connection between dietary selenium intake and CKD in adults in the USA.We included 6390 individuals from the datasets of the National Health and Nutrition Examination Survey (NHANES) between 2015 and 2018. We used multiple logistic regression, restricted cubic spline regression, and forest plots to investigate the connection between dietary selenium intake and CKD.Results: After fully adjusting the data of 6390 individuals from NHANES between 2015 and 2018, 1523 (23.83%) of the individuals were identified as having chronic kidney disease (CKD). The rates of CKD in